Colorectal cancer in adolescents and young adults with Lynch syndrome: a Danish register-based study - Thomas Kallemose; Mef Nilbert; Jon Ambæk Durhuus; Christina Therkildsen (BMJ Open)
Objective To assess clinicopathological predictors and prognosis in early-onset colorectal cancer (CRC) in Lynch syndrome with comparison to patients diagnosed from age 40 and up.Design National, retrospective register-based case–control study.Setting Danish national hereditary CRC register.Participants Individuals with Lynch syndrome diagnosed with CRC from January 1950 to June 2020. The analysis was based on 215 early-onset CRCs diagnosed between 15 and 39 years of age and 574 CRCs diagnosed at age 40–88 years.Main outcome measures Clinical and histopathological characteristics and survival. Confounding variables were analysed by Cox analysis.Results 27.2% of the tumours in the Danish Lynch syndrome cohort were diagnosed under age 40. Disease-predisposing alterations in MLH1 and MSH2 were overrepresented in the age 15–39 cohort compared with patients diagnosed over age 40. CRCs diagnosed under age 40 showed an adverse stage distribution with 36.2% stage III–IV tumours compared with 25.8% in the over age 40 group. However, young patients diagnosed with early-stage tumours did have a significantly better prognosis compared with early-stage tumours in the older age group.Conclusions Early-onset CRC in Lynch syndrome is primarily linked to alterations in MLH1 and MSH2 and displays an adverse stage distribution. These observations serve as a reminder of surveillance, symptom awareness and rapid diagnostic handling of CRC in young adults with Lynch syndrome.